Geotechnical properties of gypseous soil contaminated with crude oil. (February 2020) - Al-Adhamii, Rana A.J.; Rahil, Falah H.; Kadhim, Yasser M.; Atia, Thaer A.
Abstract: Gypseous soils are extensively distributed and especially in Iraq where area of hot climate is extant. These soils may be contaminated by crude oil due to the multiple oil wells, the oil exploitation, damaged storage tanks and pipelines, natural seepage and the crude oil spills during the war. Therefore, this study presents the geotechnical properties of gypseous soils contaminated with crude oil and the possibility of using the crude oil as an improvement material. The soil used in this study has been brought from Haditha city at Al-Anbar Governorate in Iraq with (34%) average gypsum content and classified as silty sand (SM) according to unified soil classification system (USCS). A series of laboratory tests included physical, chemical, shear strength, collapsibility test conducted on both clean and contaminated soil samples with crude oil. Compacted soil samples are prepared and three percentages of crude oil (3%, 6%, and 9%) are added to the gypseous soil samples and then tested. The results showed that the crude oil increases the liquid limit of the gypseous soils and changes the soil from non-plastic to plastic material, the crude oil also increased the maximum dry density (MDD) and decreases the optimum moisture content (OMC). The results also showed that using crude oil denotes good solution and appropriate alternate to improve the properties of gypseous soils by elimination the melting of gypsum when it comes in touch with water in addition to increase in stability and strength properties of gypseous soil by decreasing the collapse potential and increasing CBR values.